2019
DOI: 10.17718/tojde.598198
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp as a Tool for Sustainable Glocal Linguistic, Social and Cultural Interaction

Abstract: As a popular social media application, WhatsApp has become an integral part of daily lives of many people on earth. Researchers have investigated the individual, social and pedagogical benefits of the tool. However, the possible contributions of WhatsApp as a platform for cultural interaction in the glocal sense has not been examined yet. To call attention to this dimension of the tool, this case study aims to investigate the role of WhatsApp in maintaining glocal linguistic, social and cultural interaction am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, for lecturers, the use of WhatApp aims to remind students to take part in online learning (LMS Moodle) regularly and on time. The use of this media assistance in online learning) is based on several considerations, such as easy access, being able to carry out private and group chats with students, being able to carry out (online) consultations before and after lectures between teachers and (groups) of students (Kim & Nor, 2019)- (Tulgar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, for lecturers, the use of WhatApp aims to remind students to take part in online learning (LMS Moodle) regularly and on time. The use of this media assistance in online learning) is based on several considerations, such as easy access, being able to carry out private and group chats with students, being able to carry out (online) consultations before and after lectures between teachers and (groups) of students (Kim & Nor, 2019)- (Tulgar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Being remote in an online collaborative learning situation provides the learner with the possibility to unhesitatingly express their views and feelings without fear. Tulgar (2019) found that WhatsApp helps to break down barriers and increase learner participation, including the involvement of shy and introverted learners. This current study demonstrates that through the process of online collaborative learning, through WhatsApp, the learners are transformed into more effective learners, as WhatsApp promotes not only cognitive learning but also socio-emotional learning.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Tulgar (Tulgar, 2019), the use of WhatsApp in education can have several potential benefits. One benefit is the ability to facilitate communication and collaboration among students and teachers.…”
Section: Opportunitiesmentioning
confidence: 99%